OBSERVING NORMS AND ANOMY AMONG THE YOUTH: A CASE OF MADAGASCAR - Ramananarivo, Iavo (Universitas Pendidikan Indonesia, 2019)
This paper systematically addresses different concepts of anomy and norms among young men from selected groups in society. Government authorities in Madagascar who are responsible for public education are concerned about the social changes we are experiencing collectively. They have a more elaborate and better vision to guide young people in a professional and social world. In this perspective, they recognize that globalization, for example, is gradually creating a new phenomenon, in this case: technology. Many people believe that citizenship education enables adolescents to cope with these changes, since from this perspective, the child from birth is seen as part of a community, to whom he or she will eventually contribute.Â Citizenship is a mechanism that consolidates and convinces the future citizen of the importance of his social and political involvement and the valorization of his identity roots.